FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2017 - 2020 - Wahyu Indriani; Ida Nurhayati (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to find empirical evidence about the factors that affect the timeliness of the submission of financial statements. The factors tested in this study are company size, profitability, audit opinion, leverage, liquidity, company age. This study uses a quantitative method. The purpose of sampling was chosen as the sampling technique. The financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2017 – 2020 are the population in this study. This study consisted of 536 populations and through the specified criteria, 501 companies were selected as samples. From the data that has been collected then tested using logistic regression at a significant level of 5 percent. The results of this study indicate that profitability and company age significantly affect the timeliness of submitting company financial statements, while company size, audit opinion, leverage and liquidity do not significantly affect the timeliness of submitting financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2017 – 2020.